Single-junction solar cells based on p-i-n GaAsSbN heterostructures grown by liquid phase epitaxy. (15th September 2020) - Milanova, Malina; Donchev, Vesselin; Cheetham, Kieran J.; Cao, Zhongming; Sandall, Ian; Piana, Giacomo M.; Hutter, Oliver S.; Durose, Ken; Mumtaz, Asim
Highlights: P-i-n GaAsSbN/GaAs solar cells are grown by Liquid Phase Epitaxy for the first time. Temperature-dependent PL reveals shallow localized states in the bandgap of GaAsSbN. The efficiency of non-optimized solar cells without antireflection coating is 4.15% EQE measurements show that infrared spectral photosensitivity extends to 1040 nm. Abstract: In this paper, we present single heterojunction p-i-n GaAsSbN/GaAs solar cells grown by low-temperature liquid-phase epitaxy (LPE) – this is of interest as a component of multi-junction solar cell devices. The quaternary absorber layer was characterized by low excitation power photoluminescence to give the temperature dependence of the bandgap. This conformed to the Varshni function at low temperatures to within 10 meV, indicating relatively small alloy potential fluctuations. The absorption properties and the transport of the photogenerated carriers in the heterostructures were investigated using surface photovoltage method. A power conversion efficiency of 4.15% (AM1.5, 1000 W·m −2 ) was measured for p-i-n GaAsSbN/GaAs solar cells, which is comparable to the efficiency of MOCVD grown devices of this type. This is promising for the first report of LPE grown GaAsSbN/GaAs solar cells since the current record efficiency for the cells based on these compounds grown by MBE stands just at 6%. The long-wavelength photosensitivity of the cells determined from external quantum efficiency and surface photovoltage measurements was shown to be extended to 1040 nm.